Co-expression pattern of neuronal nitric oxide synthase and two variants of choline acetyltransferase in myenteric neurons of porcine ileum - Brehmer, Axel; Schrödl, Falk; Neuhuber, Winfried; Tooyama, Ikuo; Kimura, Hiroshi (Journal of Chemical Neuroanatomy, 2004)
Cholinergic enteric neurons were demonstrated immunohistochemically so far by using antibodies staining the common choline acetyltransferase (cChAT) in neurons of the central nervous system. The results of staining in the enteric nervous system of various species were, however, not satisfactory. We describe here findings obtained with a newly raised antibody against a peripheral variant of choline acetyltransferase (pChAT) in myenteric neurons of the pig small intestine. Triple labelling for pChAT/cChAT/neuronal nitric oxide synthase (nNOS) revealed 19.7% of 1664 neurons (within 40 ganglia) to be immunoreactive exclusively for pChAT whereas 29.6% were positive for cChAT alone and 18.8% were reactive only for nNOS. Colocalization of pChAT and cChAT was found in 22.4%, of pChAT and nNOS in 8.1% and of cChAT and nNOS in 1.4%. All three markers were simultaneously found in only 1 of 1664 neurons. To investigate the presence and possible colocalization of the above markers within morphologically defined neuron types, triple labelling of cChAT or nNOS with pChAT and a neurofilament (NF) antibody pool was applied and the coexpression patterns of pChAT and cChAT as well as of pChAT and nNOS in 120 neurons of each type were recorded. All type I, II, IV and V neurons displayed immunoreactivity either for one or both cholinergic markers. These neuron types were considered to be cholinergic. All type VI neurons, a descending neuron population, were negative for cChAT but positive for nNOS. However, 95% were immunoreactive for both pChAT and nNOS. The physiological significance of the possible co-existence of acetylcholine and nitric oxide within type VI neurons remains to be clarified. It is concluded that the pChAT and cChAT antibodies used here recognize partly different populations of enteric neurons in the pig. Thus, for total immunohistochemical characterization of cholinergic enteric neurons both forms of choline acetyltransferase have to be considered. © 2003 Elsevier B.V. All rights reserved.
Keywords: Acetylcholine; Cholinergic; Innervation; Intestine; Morphology; Nitrergic; Peripheral ChAT